Investigating Socialization, Work-Related Norms, and the Ethical Perceptions of Marketing Practitioners - McClaren, Nicholas (Journal of business ethics, 2010)
This study examines the influence of socialization on work-related norms (WORKNORM). We tested the hypothesis that organizational (ORGSOC) and professional socialization (PROFSOC) are antecedent influences on WORKNORM, employing a sample of 339 marketing practitioners. The results of covariance structural analysis indicate that ORGSOC and PROFSOC and WORKNORM are discriminant constructs within the tested model. The study also reveals that the influence of ORGSOC on WORKNORM is stronger than the influence of PROFSOC on these same norms. Because this social learning occurs in work-related activities, in organizations, and in professional life, it is important that managers appreciate that these three separate domains influence decision making under ethical conditions. The limitations of the study and future research directions are discussed.